(untitled) (Hekima Review, 2006)
The problem of refugees has become a big challenge for the whole of humanity, especially since the last century. The reasons for this are many, but the most common are armed conflicts, religious persecution and economic precariousness, particularly in developing countries. To cope with this situation, the international community, through United Nations, has adopted some legal instruments in order to protect those vulnerable people. Now, some questions arise: what are those instruments? What is their content? Do they adequately address the problem of refugees in its all dimensions? What are their limitations? Above all, what can be their implications on the ministry of the Church towards refugees?